The sources of Reforms of Peter I in reforms of the state administration in the government of Feodor III and in the government of regent Sofia - T. V. Chernikova (Vestnik MGIMO-Universiteta)
The article is devoted to an examination of a question of the reform of the state administration in the government of Feodor III and in the government of regent Sofia in the last quarter of XVII century. The author tries to find the parallels between the reforms of the state administration of Peter I and the reforms of the state administration of Feodor III and I and regent Sofia. The author tries to find, what were the reasons of the reforms and the results and significance of this phenomenon.